Students’ Perceptions on Benefits and Challenges in Using Google Classroom for Online English Learning during Pandemic Covid-19 - Sudaryani, Harlina; Rukmini, Dwi; Ardiasih, Lidwina Sri (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
The emergence of Covid-19 make the learning process should conducting in online. LMS is play important role as media in supporting learning process, but the readiness of students related to the use of Google classroom must be studied more deeply. This study aims to analyze the students' perceptions on Google Classroom's benefits and challenges in online English education. The researcher conducted the study during the covid-19 outbreak. This research is qualitative and descriptive. The researcher used questionnaires, interviews, and observations as the instruments to collect data. The research subjects are 72 Accounting and Finance students from vocational high school, consisting of two boys and seventy girls. The researcher distributed the questionnaire to 72 participants. The researcher then interviewed twelve students. According to the results, the process of studying English online with Google Classroom is consistent with existing learning phases. The second finding is that Google Classroom provides numerous benefits for online English learning for students. This study also revealed that the students encountered several challenges when utilizing Google Classroom for online English learning: internet connection, insufficient internet quota, internet speed, and lack of gadgets for online English learning. In this study, the researcher provided solutions to the challenges of using Google Classroom for online English learning. The solutions suggested by the researcher are Providing sufficient access to devices and internet packages and enhancing signal strength and internet speed.